Public relations programs in academic libraries in Metro Manila - Dalisay, Daisy Irabon 1958- (1996)
It is concluded that PR is new and practiced only in a few academic libraries in Metro Manila.
This study was conducted to determine whether academic libraries in Metro Manila have formal/informal PR programs. Using the survey method, 54 heads of academic libraries in Metro Manila were requested to accomplish the survey questionnaire between the second week of November 1995 and the third week of January 1996. Data obtained from the study showed that: (1) only 38 of the 54 academic libraries have formal and informal PR programs; (2) PR program is quite young in academic libraries and its growth and development is very slow compared to that of PR programs in business and industry; (3) the staff involved in PR work in academic libraries are the chief librarians/university librarians/directors or the person with the hihgest ranking position in the library but they have no any formal training in PR; (4) the assignment of PR was only an additional work to them and not primarily created for the purpose; (5) the PR activity most frequently practiced was "Formulating library policies and regulations for library users"; (6) the most frequently used PR technique is personal visits/contacts; (7) the most effective PR tool as percieved by the academic librarians are books; (8) only 15 respondents admitted that the budget figures alloted for PR activities is about one-tenth of the library budget; (9) among the four problems listed in the questionnaire, the lack or absence of the library personnel to handle the PR work ranked first.
Thesis (M.L.S.)--University of the Philippines, Diliman.
Typescript.
Vita.
Keywords: Public relations -- Libraries -- Philippines -- Manila Metropolitan Area; Academic Libraries -- Philippines -- Manila Metropolitan Area